Decabrominated diphenyl ether and methylmercury impair fetal nervous system development in mice at documented human exposure levels. Issue 1 (12th July 2014) - Mariani, Alessandro; Fanelli, Roberto; Re Depaolini, Andrea; De Paola, Massimiliano
ABSTRACT The central nervous system (CNS) is extremely vulnerable to the toxic effects of environmental pollutants during development. Polybrominated diphenyl ethers (PBDEs) are persistent contaminants, increasingly present in the environment and in human tissues. Recent investigations identified a correlation between maternal exposure to PBDEs and impairment in fetal neurobehavioral development, suggesting that these contaminants pose a potential risk for children. We investigated on the potential effects of environmental decabrominated diphenyl ether (decaBDE, the fully brominated congener) on key neurodevelopmental molecules (e.g., synaptic proteins and immature neuron markers) in fetal mouse neurons. Methylmercury was used as reference neurotoxic contaminant and to evaluate its possible synergism with decaBDE. The neurotoxic effects of decaBDE and methylmercury were determined in developing cultured neurons from mouse fetal hippocampus and cerebellum. Neuron death, dendritic branching, synaptic protein expression, markers of immature neurons, and microglia activation were evaluated by immunocytochemistry. Brain samples from prenatally treated embryos were also examined for neurotoxicity signs by immunoblotting and histochemistry. DecaBDE significantly affected (down to 0.4 nM) the number of dendritic branches, and the levels of synaptic proteins and doublecortin in cultured neurons. Prenatal exposure to decaBDE decreased the synaptic proteins and increased the expression of the immature neuron and microglial markers in mouse fetuses. In conclusion, prenatal exposure to realistic (relevant for human exposure) concentrations of decaBDE induces impairment of fetal CNS development in mice, suggesting a potential risk of fetotoxicity in humans. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 75: 23–38, 2015